2019
DOI: 10.3126/irjms.v4i0.27883
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Brain Drain and its Impact on the Sending Economy: A Case Study of Nepal

Abstract: The research attempts to examine the factors that lead the experts to leave the country. Using 160 respondents living abroad, the study investigates the relationship between brain drain and the sending economy i.e. Nepal. The study follows descriptive, co-relational and causal comparative research design to analyze the purpose of this study. The result reveals that people leave country mainly for the purpose of education, employment and skills but what makes them settle there is employment and skills, as both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Nepal is currently facing the imminent loss of its young and potential workforce on a regular basis (Silwal, 2019). Very few female and male youth are working in foreign employment comparing to Mountain and Hill regions.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal is currently facing the imminent loss of its young and potential workforce on a regular basis (Silwal, 2019). Very few female and male youth are working in foreign employment comparing to Mountain and Hill regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study found that there is a significant association between economy and their employability based on their skills. Hence, they choose skilled based employment rather than continuing their studies in the destination countries (Silwal, 2019).…”
Section: Pursue Studymentioning
confidence: 99%